Research and development in culture : a case for cross subsidies in the arts (2009)
Several types of arguments advocate state involvement in the promotion of culture. Many of them imply some sort of subsidy, usually to non-for-profit firms; none favors taxing cultural events. The tax literature, on the other side, discusses excise taxation on culture only as a way to redistribute income. However, to the extent that culture is a public good, taxing it is undesirable. Why are then excise taxes on public events extant in many countries? This paper argues that the development of profitable artists is analogous to R&D in the industrial organization literature, and that the excise taxation of public cultural events may be part of an efficient policy to fund it. Using a Stackelberg game to model the investment to develop an artist, I find that the optimal tax is a multiple of the expected surplus created by the artist that cannot be appropriated by the investor who funds her, and that progressivity plays a limited role at most.